CD36 Is a Matrix Metalloproteinase-9 Substrate That Stimulates Neutrophil Apoptosis and Removal During Cardiac Remodeling. (February 2016) - DeLeon-Pennell, Kristine Y.; Tian, Yuan; Zhang, Bai; Cates, Courtney A.; Iyer, Rugmani Padmanabhan; Cannon, Presley; Shah, Punit; Aiyetan, Paul; Halade, Ganesh V.; Ma, Yonggang; Flynn, Elizabeth; Zhang, Zhen; et al.
Abstract : Background—: After myocardial infarction, the left ventricle undergoes a wound healing response that includes the robust infiltration of neutrophils and macrophages to facilitate removal of dead myocytes as well as turnover of the extracellular matrix. Matrix metalloproteinase (MMP)-9 is a key enzyme that regulates post-myocardial infarction left ventricular remodeling. Methods and Results—: Infarct regions from wild-type and MMP-9 null mice (n=8 per group) analyzed by glycoproteomics showed that of 541 N -glycosylated proteins quantified, 45 proteins were at least 2-fold upregulated or downregulated with MMP-9 deletion (all P <0.05). Cartilage intermediate layer protein and platelet glycoprotein 4 (CD36) were identified as having the highest fold increase in MMP-9 null mice. By immunoblotting, CD36 but not cartilage intermediate layer protein decreased steadily during the time course post-myocardial infarction, which identified CD36 as a candidate MMP-9 substrate. MMP-9 was confirmed in vitro and in vivo to proteolytically degrade CD36. In vitro stimulation of day 7 post-myocardial infarction macrophages with MMP-9 or a CD36-blocking peptide reduced phagocytic capacity. Dual immunofluorescence revealed concomitant accumulation of apoptotic neutrophils in the MMP-9 null group compared with wild-type group. In vitro stimulation of isolated neutrophils with MMP-9 decreased neutrophil apoptosis, indicated by reduced caspase-9 expression. Conclusions—: Our data reveal a new cell-signaling role for MMP-9 through CD36 degradation to regulate macrophage phagocytosis and neutrophil apoptosis. Abstract : Supplemental Digital Content is available in the text.